Data from: Ice-nucleating particles near two major dust source regions. In Center for Aerosol Impacts on Chemistry of the Environment (CAICE) ... - Beall, Charlotte; Hill, Thomas C. J.; DeMott, Paul J.; Könemann, Tobias; Pikridas, Michael; Drewnick, Frank; Harder, Hartwig; Pöhlker, Christopher; Lelieveld, Jos; Weber, Bettina; Iakovides, Minas; Prokes, Roman; et al. (UC San Diego Library Digital Collections, 2022)
Publication abstract: Mineral dust and sea spray aerosol are important sources of ice nucleating particles (INPs), the small fraction of aerosol particles able to trigger cloud ice crystal formation and consequently, influence multiple climate-relevant cloud properties including lifetime, reflectivity and precipitation efficiency. Mineral dust is considered the dominant INP source in many parts of the world due to its ice nucleation efficiency and its sheer abundance, with global emission rates of up to 4700 Tg a-1. However, INPs emitted from the ocean surface via sea spray aerosol frequently dominate INP populations in remote marine environments, including parts of the Southern Ocean where cloud-resolving model simulations have demonstrated that cloud reflectivity is likely strongly controlled by INPs. Here we report INP concentrations measured in aerosol and seawater samples during Air Quality and Climate Change in the Arabian BAsin (AQABA), a shipborne campaign that spanned the Red Sea, Gulf of Aden, ... : Back-trajectory analysis completed with FLEXPART: https://www.flexpart.eu/. Analyses and visualizations of dust mass concentrations and Chl a used in this paper were produced with the Giovanni online data system, developed and maintained by the NASA GES DISC. ...